2003
DOI: 10.1002/marc.200300014
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Binary Conductive Polymer Composites with Very Low Percolation Threshold by Latex Blending

Abstract: The communication reports a way to prepare carbon black (CB)/waterborne polyurethane conducting composites with percolation thresholds as low as 0.2 vol.‐% through conventional latex blending. CB particles in the composites appear segregated in their distribution and are located in the two‐dimensional interstices among the polymer domains. The intimate filler/matrix interaction also improves the tensile strength of the matrix at the CB content corresponding to the electrical percolation threshold.Room temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Up to now, there have been many investigations on reducing the percolation threshold by manipulating the distribution of CB particles, such as multipercolation, [19][20][21][22] segregated distribution, 14,17,23 and electrical field-induced method, 24 etc. Multipercolation is an effective technology through melt mixing method.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, there have been many investigations on reducing the percolation threshold by manipulating the distribution of CB particles, such as multipercolation, [19][20][21][22] segregated distribution, 14,17,23 and electrical field-induced method, 24 etc. Multipercolation is an effective technology through melt mixing method.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new approach to incorporate nanoscale fillers into a polymer matrix was developed using latex technology [4,15,16]. The latex particles (diameters ~10 to 1000 nm) are suspended in water with nanofillers, and upon drying, the fillers occupy the interfacial and interstitial regions between the latexes.…”
Section: Introductionmentioning
confidence: 99%
“…The sample geometries were 1 Â 10 Â 10 and 1 Â 80 Â 80 mm 3 for the four-point probe and high-resistance meter, respectively. The 1 Â 10 Â 80 mm 3 samples were used in resistivity-temperature behavior testing, for which a WCY-SJ temperature programming control system (Nanjing Sangli Electronic Equipment Works, Nanjing, China) was used; the heating medium was silicone oil, the samples were immersed in it to avoid oxidation, and the testing temperature ranged from room temperature to 180 C at a heating rate of 2 C/ min.…”
Section: Measurements and Characterizationmentioning
confidence: 99%
“…For example, Yoon et al 1 reported that the electrical conductivity of carbon black (CB)/polymer composites is tremendously influenced by the amine-terminated coupling treatment of CB because of its action as an assister of electrical conduction. Grunlan et al 2 and Hu et al 3 found that mixing CB and polymer suspensions or emulsions under highspeed stirring could lead to a low percolation threshold because of conductive pathway formation during the drying of the latex. Tjong et al 4 and Hu et al 5 reduced the percolation threshold of polypropylene (PP)/multiwalled nanotube and poly(ethylene terephthalate)/multiwalled nanotube nanocomposites by high-shear-rate processing and coagulation, respectively.…”
Section: Introductionmentioning
confidence: 98%